Assessment on Level of Acceptability of Cupcake Made from Jackfruit Seed Flour (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Jackfruit (Artocarpus heterophyllus) is a common fruit that is found in the Philippines. Jackfruit seeds are good sources of important nutrients such as carbohydrates, dietary fibers, antioxidants, vitamin A, vitamin B, vitamin C, and some minerals. In this study, jackfruit seeds were dried and powdered to produce jackfruit seed flour. The researchers used jackfruit seed flour as a main ingredient of baking cupcakes. The research was experimental. The researchers used a random sampling technique to select therespondents. They also used a survey questionnaire for data collection. In terms of taste, the respondents had a weighted mean of3.32, which indicated that the product was acceptable. In terms of aroma, the respondents had a weighted mean of3.55, which indicated that the product was highly acceptable. In terms of nutritional value, the respondents had a weighted mean of4.02, which indicated that the product was highly acceptable. In terms of competitiveness, the respondents had a weighted mean of4.35, which indicated that the product was highly acceptable. In terms of presentation, the respondents obtained a weighted mean of4.22, which indicated that the product was highly acceptable. The composite grand mean of the respondents was 3.75, which indicated that the product was highly acceptable. In terms of the level of acceptability, the respondents rated jackfruit seed flour as highly acceptable. The aroma of the jackfruit seed flour is highly acceptable, with no bitter aftertaste. The researchers recommended that future studies should further refine the product in terms of marketability, competitiveness, and presentation.
Keywords: jackfruit, seed, flour, common fruit